MANAGING WORK-LIFE BALANCE TO OPTIMIZE EMPLOYEE WELFARE AND PRODUCTIVITY - Apriani Paskawati; Salju; Rismawati; Goso; Rahmawati, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study investigates the impact of work-life balance on employee well-being and productivity within the public sector, specifically focusing on the East Luwu Regency. Utilizing Structural Equation Modeling (SEM), the research examines how work-life balance contributes to employee welfare and overall productivity. The study draws on data collected from 200 employees across various departments within the local government. The results reveal that work-life balance significantly and positively influences both employee well-being and productivity, with the SEM model indicating that 51.5% of the variance in well-being and 55.0% in productivity can be explained by work-life balance. These findings underscore the critical role of work-life balance in enhancing employee outcomes and highlight the need for local governments to adopt more flexible and supportive work policies. The research contributes to the broader understanding of organizational behavior within the public sector and offers practical recommendations for improving employee welfare and productivity through better work-life balance strategies.